Enhancing Long-Read-Based Strain-Aware Metagenome Assembly - Luo, Xiao; Kang, Xiongbin; Schönhuth, Alexander (Frontiers in Genetics, 2022)
Microbial communities are usually highly diverse, and often involve multiple strains from the participating species due to the rapid evolution of microorganisms. In such a complex microecosystem, different strains may show different biological functions. While reconstruction of individual genomes at the strain level is vital for accurately deciphering the composition of microbial communities, the problem has largely remained unresolved so far. Next generation sequencing has been routinely used in metagenome assembly, but struggles to generate strain-specific genome sequences due to the short read length. This explains why long-read sequencing technologies have recently provided unprecedented opportunities to carry out haplotype- or strain-resolved genome assembly. Here, we propose MetaBooster and MetaBooster-HiFi, as two pipelines for strain aware metagenome assembly from PacBio CLR and Oxford Nanopore long-read sequencing data. Benchmarking experiments on both simulated and real sequencing data demonstrate that either the MetaBooster or the MetaBooster-HiFi pipeline drastically outperform the state of the art de novo metagenome assemblers, in terms of all relevant metagenome assembly criteria, involving genome fraction, contig length and error rates.